Subchronic Stimulation Performance of Transverse Intrafascicular Multichannel Electrodes in the Median Nerve of the Göttingen Minipig. Issue 2 (23rd July 2014) - Harreby, Kristian R.; Kundu, Aritra; Yoshida, Ken; Boretius, Tim; Stieglitz, Thomas; Jensen, Winnie
Abstract This work evaluated the subchronic stimulation performance of an intraneural multichannel electrode (transverse intrafascicular multichannel electrode, TIME) in a large human‐sized nerve. One or two TIMEs were implanted in the right median nerve above the elbow joint in four pigs for a period of 32 to 37 days (six TIMEs in total). The ability of the contact sites to recruit five muscles in the forelimb was assessed via their evoked electromyographic responses. Based on these responses, a selectivity index was defined. Four TIMEs were able to selectively recruit a subset of muscles throughout the implantation period. The required recruitment current significantly increased, while there was a tendency for the recruitment selectivity to decrease over time. Histological assessment showed that all TIMEs remained inside the nerve and that they were located between fascicles. The average thickness of the encapsulation of the electrode was estimated to be 115.4 ± 51.5 μm (mean ± SD). This study demonstrates the feasibility of keeping the TIME electrodes fixed and functional inside a large polyfascicular human‐sized nerve in a subchronic setting.